ANALISIS KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN TANIHUB FOOD SOLUTIONS DI JAKARTA SELATAN - Tiara Oktaviani (2022)
The purpose of this study is to determine the impact of service quality on customer loyalty at TaniHub Food Solutions in South Jakarta through customer satisfaction analysis using a quantitative method with a questionnaire distribution method. This study focused on fruit and vegetable traders in South Jakarta, with a total of 100 respondents. The sampling in this study was non-probability based on a purposive sampling approach. In this study, data analysis was performed using SmartPLS 3.0. The PLS approach incorporates two stages of hypothesis testing: outer and inner models. The outer model test proves the validity and reliability of each indicator. An inner model test measures the influence between variables in relation to the hypotheses that have been previously constructed. As a result, (1) Service quality is positively and significantly correlated with customer loyalty, (2) Service quality is positively and significantly correlated with customer satisfaction, (3) Customer satisfaction is positively and significantly correlated with customer loyalty, and (4) Quality services indirectly have a positive and significant influence on customer loyalty.